The search for scrapie agent nucleic acid. - Aiken, J M (1990)
Despite decades of research, the identity of the scrapie agent has remained elusive. Recent studies have discovered much about the influence of the host genome upon scrapie infection, yet relatively little is known about the causative agent itself. The predominant hypothesis in the scrapie field (the prion hypothesis) argues that the disease is the result of an infectious protein and that nucleic acid is not required for infection. Biological studies of the scrapie agent, however, suggest that a nucleic acid may be involved in the disease. Sensitive molecular biology techniques have yet to identify this putative nucleic acid.